PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PBL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DALAM MEMAHAMI ISI CERITA PENDEK PADA SISWA KELAS 3 SD NEGERI LABANG - Anggi Eva Mukharomah; Siti Nur Fauziyah; jamal alrs muhammad jamal al rosyid (Yayasan Pondok Pesantren Nurul Islam Mojokerto, 2023)
This study aims to determine how the application of a cooperative learning model of problem- based learning type on the ability to read and understand the content of short stories in third grade students of SDN Labang. The research method used Classroom Action Research (PTK) referring to the Kurt Lewin model. The research subjects were 39 students and 1 teacher of grade III SDN Labang, as well as the principal of SDN Labang. The data collection techniques used interviews, observations, documentation, and tests using research instruments question sheets, observation sheets, lesson plans, student reading observation sheets, and question sheets. the results of the reading and comprehension ability test in cycle 1 there were 4 groups out of 5 groups that had not reached a score of 70%, so they still did not reach the predetermined target score. In cycle 2 there was an increase from the previous cycle where each group had managed to reach the predetermined target score of 70%. It can be concluded that the application of cooperative learning model of problem- based learning type can improve the ability to read and understand the content of short stories in grade III students.